Interactive Book Design For Child Speech Delay Therapy - Leonardo Adi Dharma Widya; Prasna Juwita (ULTIMART Jurnal Komunikasi Visual, 2023)
The ability of speech is influenced by intrinsic and extrinsic factors. If the two factors do not support the development of speech in the child, then the speech ability will be late, which is called speech delay. If speech delay is not addressed immediately, then the impact will continue until the child is an adult. Therefore, interactive book design has a purpose as a media of stimulation that can be used by children and parents. This research will raise topics about the creation and application of interactive visuals in books. The results of this study are expected to be played by parents with children on a regular basis so that the features of this interactive book can be used effectively until the child is interested in learning to recognize and pronounce words or sentences and at the same time helps improve fine motor skills in the child. Keywords : speech delay; interactive; book; stimulation